Clinical Phenotype and Mutation Spectrum of Alzheimer’s Disease with Causative Genetic Mutation in a Chinese Cohort - Mao, Chenhui; Li, Jie; Dong, Liling; Huang, Xinying; Lei, Dan; Wang, Jie; Chu, Shanshan; Liu, Caiyan; Peng, Bin; Román, Gustavo C.; Cui, Liying; Gao, Jing (Current Alzheimer Research, 2021)
Background: Alzheimer’s disease with a causative genetic mutation (AD-CGM) is an uncommon form, characterized by a heterogeneous clinical phenotype and variations in the genotype of racial groups affected. Objective: We aimed to systemically describe the phenotype variance and mutation spectrum in the large sample size of the Peking Union Medical College Hospital (PUMCH) cohort, Beijing, China. Methods: Next-generation sequencing (NGS) was carried out in 1108 patients diagnosed with dementia. A total of 40 Han Chinese patients with three AD gene mutations were enrolled. A systemic review of all the patients was performed, including clinical history, neurocognitive assessment, brain magnetic resonance imaging, and cerebrospinal fluid (CSF) biomarkers. Results: We studied the following gene mutation variants: 12 AβPP, 13 PSEN1, and 9 PSEN2, and 23 among them were novel. Most of them were early-onset, but PSEN1 mutation carriers had the youngest onset age. The commonest symptoms were similar to those of AD, including an amnestic syndrome, followed by psychiatric symptoms and movement disorder. On MRI, parietal and posterior temporal atrophy was prominent in PSEN1 and PSEN2 mutation carriers, while AβPP mutation carriers had more vascular changes. The CSF biomarkers profile was indistinguishable from sporadic AD. Conclusion: We identified a small group of AD-CGM subjects representing 3.6% among more than 1000 demented patients in the PUMCH cohort. These subjects usually presented with early-onset dementia and exhibited significant clinical and genetic heterogeneity. Identification required complete screening of genetic mutations using NGS. Although family history was usually present, we found non-familial cases of all three genetic mutations.
Keywords: causative genetic mutation